Impact of Control on Healthcare Expenses and quality of care in Lebanon: Case of Health Insurance - Gemayel, Joseph; Nohra, Dunya; Khattar, Josiane Abi; Nehme, Maha; Khawaja, Danie (Technium Social Sciences Journal, 2026)
Background: The efficient management of financial resources and the delivery of quality care are crucial challenges in healthcare. Health insurance companies in Lebanon play a significant role in ensuring medical care through contracted hospitals. Objective: This study assesses the impact of control mechanisms implemented by Health insurance companies on healthcare expenses and the quality of care provided in Lebanon. Methods: A cross-sectional analytical study was conducted with a census of 50 Health insurance controllers working in various contracted hospitals. Data collection was performed using a structured questionnaire. Statistical analysis included descriptive and inferential tests to assess the associations between variables, with significance set at p < 0.05. Results: The findings reveal that health insurance controllers significantly influence cost reduction and quality improvement in healthcare services. Key factors, such as the type of hospital and the number of insured patients, were associated with control effectiveness. Conclusion: Control mechanisms by health insurance controllers in Lebanon have demonstrated a positive impact on healthcare expenses and quality of care, highlighting the need for sustained efforts to optimize these practices.